Revascularization of an immature tooth with apical periodontitis using a single visit protocol: a case report. (27th August 2014) - McCabe, P.
Abstract Aim To discuss the clinical and radiological outcome of a revascularization procedure which was completed in a single visit (using sodium hypochlorite 5% as the sole disinfectant) in an immature tooth with a necrotic pulp and apical periodontitis. Summary A 7‐year‐old girl was referred in pain following trauma to the maxillary anterior region some 6–7 weeks previously. The maxillary left central incisor tooth was diagnosed with a necrotic pulp and acute apical periodontitis. Under local anaesthesia and rubber dam isolation, an access cavity was prepared. The canal was irrigated with a 5% sodium hypochlorite solution and agitated with an ultrasonic file. A 17% EDTA solution was also used for a final rinse. Bleeding was induced into the canal space from the periapical tissues using a K‐file. An MTA layer/barrier was placed directly onto the blood clot, and a further layer of GC Fuji IX cement was placed on top of the MTA to restore the access cavity. The tooth was reevaluated at 6 weeks, 3 months, 6 months, 1 year and 18 months. The tooth has remained symptom free. Radiographic examination shows progressive thickening of the root canal walls, root lengthening and apical closure. Key learning points Disinfection with 5% sodium hypochlorite followed by the induction of a blood clot into the root canal space may be sufficient to promote revascularization in certain circumstances. A single visit revascularization procedure is a potential treatment option.